Cruel traces: Bone surface modifications and their relevance to forensic science. Issue 3 (25th October 2020) - Egeland, Charles P.; Pickering, Travis Rayne
Abstract: The reconstruction of perimortem and postmortem events is of critical importance to criminal investigations. In many cases, the information required for these reconstructions can be accessed through the analysis of skeletal remains. One particular class of skeletal data—trauma to the surfaces of bones, or bone surface modifications (BSMs)—can reveal much about the perimortem and postmortem intervals. While the study of BSMs originated within the fields of paleontology and archeology and was only later integrated into forensic science, a fruitful interdisciplinary exchange of data and methods is now commonplace. BSMs from thermal alteration, sharp‐force trauma, terrestrial and aquatic scavengers and predators, bacteria and fungi, insects, weathering, and sediment abrasion can supply investigators with valuable information about the agents and events of a corpse's deposition, including weapon type, local environmental conditions, the postmortem interval, and the presence, temperature(s), and/or length(s) of thermal exposure. Based on a review of this rich body of literature, we argue that (a) all associations between a BSM and its alleged source must rest on observational cause‐and‐effect studies; (b) secure identifications of BSMs should rely both on the intrinsic features of the modifications themselves and relevant contextual data; (c) the scientific validity of BSM research depends, ultimately, on rigorous blind‐testing and the establishment of error rates; and (d) researchers need to make a concerted effort to enhance interanalyst correspondence through objective definitions, measurements, and/or codes of BSM features. The most promising path forward lies in the combination of digital image analysis and multivariate predictive modeling. This article is categorized under: Forensic Anthropology > Trauma Analysis Forensic Anthropology > Taphonomic Changes and the Environment Forensic Anthropology > Time Since Death Estimation Abstract : Bone surface modifications like this kerf produced by a wavy‐set hacksaw on a human femur provide forensic investigators with a wealth of information on the perimortem and postmortem events surrounding the deposition of a corpse.